2020
DOI: 10.1186/s12992-020-00616-w
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating violence against women and young girls during COVID-19 induced lockdown in Nepal: a wake-up call

Abstract: Nepal, a South Asian country, was in nationwide lockdown for nearly three months in 2020 with partial restrictions still in place. Much worryingly, COVID-19 induced restrictions have confined women and young girls in their home, increasing the risk of domestic violence. The available support system to respond to violence against women and girls (VAWG) has also been disrupted during this period. The figures of violence against women, and child sexual abuse are increasingly being reported during the lockdown and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 4 publications
2
33
0
9
Order By: Relevance
“…Moreover, of pivotal importance are the maintenance and support of both clinical and forensic services for survivors of violence despite the modifications to the provision of health care services because of the new needs due to the COVID-19 pandemic [ 28 , 17 , 51 , 36 , 43 ], as well as the redefinition of safe shelters [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, of pivotal importance are the maintenance and support of both clinical and forensic services for survivors of violence despite the modifications to the provision of health care services because of the new needs due to the COVID-19 pandemic [ 28 , 17 , 51 , 36 , 43 ], as well as the redefinition of safe shelters [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our review found how the dynamics of DV were explored in several studies (Anurudran et al 2020;Bouillon-Minois et al 2020;Bright et al 2020;Campbell et al 2020;Da Silva et al 2020;Dahal et al 2020;Duncan et al 2020;Ertan et al 2020;Evans et al 2020;Joseph et al 2020;Moreira et al 2020;Sacco et al 2020;Usher et al 2020). Indeed, self-isolation and social distancing can put women in constant danger by mandatory proximity with the perpetrator and isolating them from protective factors such as moments of relative freedom or access to support.…”
Section: Resultsmentioning
confidence: 94%
“…Violence against young girls causes physical and psychological effects, which can manifest as mild anxiety symptoms, apprehension, flashbacks, or feeling ashamed or worried to more severe anxiety signs, including a variety of sleep or eating disorders, post-traumatic symptoms, and even thoughts of self-harm and suicide. The inaction of a valid support system may further worsen this complex situation[ 8 ].…”
Section: Exposure Of Children To Parental Domestic Violencementioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) has had a dreadful impact on the world’s economy, and women are forced to take on additional risks as they are already disadvantaged and vulnerable, especially in rural and remote settings[ 8 ]. Sexuality suffers because it has to deal with the arrogance of a death drive rekindled by the current pandemic condition.…”
Section: Exposure Of Children To Parental Domestic Violencementioning
confidence: 99%
See 1 more Smart Citation